In the Rat, Chronic Intermittent Ethanol Exposure During Adolescence Alters the Ethanol Sensitivity of Tonic Inhibition in Adulthood - Fleming, Rebekah L. (2011)
BACKGROUND: Alcohol drinking by adolescents is a major public health concern. Adolescents tend to drink in a chronic, intermittent, that is, “binge,” pattern, and such patterns of ethanol exposure are associated with increased risk of neurotoxicity and the development of alcohol use disorders (Crews et al., 2000; Hunt, 1993). Both adolescent humans and rats are more sensitive to acute ethanol-induced memory impairment than adults (Acheson et al., 1998; Markwiese et al., 1998). Furthermore, in rats, chronic intermittent ethanol (CIE) exposure during adolescence produces a long-lasting, perhaps permanent, maintenance of the adolescent high sensitivity to ethanol’s amnestic effects (White et al., 2000a). We have previously shown that acute ethanol increases tonic inhibitory current mediated by extrasynaptic GABA(A) receptors more efficaciously in dentate granule cells (DGCs) from adolescent than adult rats (Fleming et al., 2007). In this study, we determined if CIE during adolescence produced long-lasting changes in this tonic current. METHODS: Adolescent rats were subjected to a CIE exposure regimen and allowed to mature to full adulthood. Whole-cell voltage-clamp measurements of tonic inhibitory current and mean phasic current were made in vitro in hippocampal brain slices. RESULTS: CIE exposure during adolescence increased the ethanol sensitivity of tonic inhibitory current mediated by extrasynaptic GABA(A) receptors and decreased the ethanol sensitivity of phasic, synaptic GABA(A) receptor-mediated current in adult DGCs. CONCLUSIONS: CIE exposure during adolescence produces long-lasting changes in the function and ethanol sensitivity of extrasynaptic GABA(A) receptors in DGCs. These changes appear to “lock-in” and maintain the high adolescent sensitivity to ethanol in these cells. Furthermore, greater ethanol enhancement of tonic inhibition in the hippocampal formation after CIE is consistent with the greater sensitivity to ethanol-induced memory impairment after adolescent CIE. This finding represents the first demonstration of a long-term, memory-related cellular effect of CIE during adolescence, and the “lock-in” of adolescent ethanol sensitivity that these results suggest could represent a conceptual step forward in understanding the vulnerability of the adolescent brain to alcohol.